Kinetics and physico-chemical properties of white-rot fungal laccases - Bar, Marièlle (University of the Free State, 2001)
Laccase (EC 1.10.3.2, p-diphenol oxidase) is one of a few enzymes that have been studied since the nineteenth century. Yoshida first described laccase in 1883 when he extracted it from the exudates of the Japanese lacquer tree, Rhus vernicifera. (Thurston, 1994; Levine, 1965). In 1896 laccase was demonstrated to be a fungal enzyme for the first time by both Bertrand and Laborde (Thurston, 1994; Levine, 1965). Laccase is a member of the large blue copper proteins or blue copper oxidases, which comprise a small group of enzymes. Other enzymes in this group are the plant ascorbate oxidases and the mammalian plasma protein ceruloplasmin (Thurston, 1994; Xu, 1996; Ducros et al., 1998). Laccases are either mono or multimeric copper-containing oxidases that catalyse the one-electron oxidation of a vast amount of phenolic substrates. Molecular oxygen serves as the terminal electron acceptor and is thus reduced to two molecules of water (Ducros et al., 1998). The ability of laccases to oxidise phenolic compounds as well as their ability to reduce molecular oxygen to water has lead to intensive studies of these enzymes (Jolivalt et al., 1999; Xu, 1996; Thurston, 1994). The biotechnological importance of these enzymes can also be attributed to their substantial retention of activity in organic solvents with applications in organic synthesis. Laccases have widespread applications, ranging from effluent decolouration and detoxification to pulp bleaching, removal of phenolics from wines and dye transfer blocking functions in detergents and washing powders, many of which have been patented (Yaver et al., 2001). The biotechnological application of laccase has been expanded by the introduction of laccase- mediator systems, which are able to oxidise non-phenolic compounds that are otherwise not attacked and are thus able to degrade lignin in kraft pulps (Bourbonnais and Paice, 1990).
Dissertation (M.Sc. (Microbiology and Biochemistry))--University of the Free State, 2002
Keywords: Lignin -- Biodegradation; Basidiomycetes; Oxidoreductases; Laccases; Fungal; White-rot; Physico-chemical properties; Kinetics